Evaluation of the Psychological Empowerment among Nurses at Primary Health Care Centers - Jummha, Kamal J. Ameen; Hussein, Hassan Ali (Iraqi National Journal of Nursing Specialties, 2023)
Objective(s): This study aimed to evaluate the level of psychological empowerment among nurses as perceived by their point of view, and identify the differences in their psychological empowerment in terms of their age, gender, education and years of employment.Methodology: A descriptive evaluation design was conducted on nurses at Psycho-social Health Units in Primary Health Care Centers in Kirkuk Governorate. A convenience sample of 84 nurses was selected. The data was collected through the self-report method for the period from 25th August to 10th October 2022. The questionnaire was adopted and modified for achieving the current study’s goal; it was composed of “Socio-demographic” variables, and the Psychological Empowerment Scale (PES). Face and content validity of the questionnaire was conducted by a panel of experts, also the reliability had been evaluated, through the SPSS (Version 26) by applying Cronbach’s Alpha coefficient, which was (α = 0.81). The descriptive data was determined through Frequency, percentage, mean of the score, and standard deviation. Inferential data analysis approach: - used by enforcement of the “independent t-test” and “Analysis of Variance” (ANOVA).Results: - The results found that 66.7% of nurses perceive a high level of "psychological Empowerment", and there is a significant difference in overall "psychological empowerment" related to "age group" (50-59) years of nurses, however, there is a highly significant difference in overall "psychological empowerment" concerning their years of employment in (6-10) years.Conclusions: Highlights the importance of psychological empowerment as a strong indicator of positive organizational behavior of nurses, which can increase their self-efficacy of them, ultimately leading to improvement and elevation of the efficiency of care provided.Recommendations: It is recommended that a periodic and comprehensive evaluation of nursing staff be conducted to take appropriate means to provide a supportive work environment in order to retain the perceived high psychological empowerment among them to ensure the continuity of quality of care.